Language acquisition by Roma-Slovak bilingual children over time and by three types of Roma communities - Samko, Milan; Rosinský, Rastislav (East European Journal of Psycholinguistics, 2023)
This research aims to determine the significance of the progress in the first and second language acquisition by Roma-Slovak bilingual children in their first year of schooling, differentiated by three types of Roma communities (type 1, type 2 and type 3) at the beginning of the school year (test) and the end of the school year (post-test). The partial aim is to analyze the context and relationships of the progress in the first and second language acquisition by Roma children, determined by the type of Roma community in which individual children live. The research set as a whole (n = 68) consists of Roma-Slovak bilingual children with Romani as their native language and Slovak as their second language in their first year of schooling. Subsequently, the research set is differentiated into three groups by the type of Roma community in which the children live, namely: type 1 - municipal and urban concentrations (n = 22); type 2 - settlements located on the outskirts of a city or municipality (n = 23); and type 3 - settlements spatially remote or separated by a natural or artificial barrier (n = 23). We used a standardized research tool, OOS Test - image-vocabulary test (Kondáš, 2010). We conducted the research in two phases, at the beginning of the school year (test) and the end of the school year (post-test). To analyze the data statistically, we used the SPSS 20.0 statistical program. As one of the important findings, this study has shown statistically significant differences between Roma-Slovak bilingual children from type 1, type 2 and type 3 Roma communities in L1 and L2 at the beginning and the end of the school year. Moreover, the research has shown statistically significant differences in the acquisition progress in L1 and L2 between children from the type 1, type 2 and type 3 communities at the given time. The main research problem arising from the findings is that the progress in the first and second language acquisition by Roma-Slovak bilingual children is determined by the type of Roma community in which the Roma children live. Furthermore, the findings show a relationship and connection between the first and second language acquisition development and the type of Roma community in which the children live. AcknowledgmentsThis paper is an output of the research project "Language and Communication Problems in Slovakia and their Management" funded by the Slovak Research and Development Agency under the contract No. APVV-17-0254 (2018 – ).It is the continuation of the research project "Language competence of the Romani pupils in the first grade of primary schol" funded by the same agency under the contract No. VEGA 1/0845/15 (2015–2017).Disclosure statementNo potential conflict of interest was reported by the authors.* Corresponding author: Milan Samko,  0000-0002-1574-0672 msamko@ukf.sk